Tukholma - Belanger, Louis; Merigot, J.; Skjöldebrand, Anders Fredrik; Acerbi, Giuseppe; Saint Morys, Étienne Bourgevin Vialart de
fyysinen kuvaus: vaaka
Keywords: maisema; kaupungit; purjelaivat; Ruotsi, Tukholma, Ruotsi, Tukholma